The influence of organizational structure on value-based management sophistication. (September 2022) - Nowotny, Steven; Hirsch, Bernhard; Nitzl, Christian
Abstract: Despite the widespread use of value-based management (VBM) in European companies, studies investigating the reasons for the differences in its sophistication remain scarce and are predominantly focused on environmental and intra-organizational aspects. Since the structure of a firm as a major organizational determinant is assumed to have a considerable impact on the fit between an organization and an administrative innovation, we examine the influence of organizational structure on VBM sophistication. Based on survey data from 117 large for-profit firms in Austria, Germany and Switzerland, our findings indicate that the organizational structure variables centralization, formalization and horizontal integration are positively associated with VBM sophistication. Our data provide insight into the interconnection of specific organizational structure variables on particular VBM subdimensions. The findings illustrate that a high level of centralization is positively associated with the political fit of an organization with VBM, while vertical differentiation seems to have a negative relationship with the cultural fit with VBM. High levels of formalization and horizontal integration indicate a technical, political and cultural fit with VBM, which helps to achieve and prevail a high extent of VBM implementation in late diffusion stages. While firms that are listed on the stock market show a positive association with VBM sophistication, the interconnections of organizational structure variables with VBM sophistication appear both in listed and unlisted firms.